'Time of My Life?' The afterlife of Dirty Dancing in the contemporary romantic comedy. Issue 2 (1st October 2014) - Smith, Frances
Released in 1987, the continued popularity of Dirty Dancing by Emile Ardolino, and its associated soundtrack cannot be disputed. David Shumway's analysis of the film's soundtrack argues that its newly produced songs, such as '(I've Had) the Time of My Life' performed by Bill Medley and Jennifer Warnes, rupture the purported realism of the film's 1963 setting in favour of idealized fantasy. Exploring the implications of Shumway's claim, this article examines how Dirty Dancing's theme song has been taken up in two contemporary romantic comedies – Crazy Stupid Love by Glenn Ficarra and John Requa (2011), and Heartbreaker by Pascal Chaumeil (2010) – in which it is used by the male protagonists in order to win favour with their prospective partners. Combining Judith Butler's work on performativity and citationality with the work of Ian Garwood and Frank Krutnik on the role of quotation in the recent romantic comedy and Rick Altman's and Richard Dyer's work on the film musical, the article observes how in both films, the male characters appeal directly to the women's enjoyment of Dirty Dancing, culminating in scenes where the male and female leads perform a dance to '(I've had) the Time of My Life'. Complicating the dominant perception of the use of older songs in the contemporary romantic comedy, the article investigates the complex legacy of a hugely popular film whose eclectic soundtrack has seen relatively little academic interest.